Economic emergency in East Asia and its impact on international relations. - Zhenxing, Su (1997)
In this text, the author discusses the impact of the emerging economy of East Asia in international relations. In this respect, he analyzes the behavior of gross domestic product and foreign trade in the most important countries and areas of the world; likewise, the main impact of the changes in international relations in the regional scope.   According to these considerations, the author concludes that although it is not yet possible to conceive such impact in the long run, the changes produced so far are strong enough as to modify the structure of contemporary relations.